Microwave Pulse Energy Compression; AMEREM '96 : high power electromagnetics, nuclear electromagnetics, ultra-wideband, short-pulse electromagnetics 3, unexploded ordnance detection & range remediation, Albuquerque, New Mexico, 27-31 May, 1996 - Didenko A. N. Andrei Nikolaevich (1996, 1996)
В фонде НТБ ТПУ отсутствует